Effects of Trade Agreements and Foreign Direct Investment on Trade: Evidence from Vietnam - Duong, My; Holmes, Mark J.; Strutt, Anna; Lim, Steven (International Journal of Economics and Financial Issues, 2019)
In recent years, Vietnam has embarked on trade liberalisation leading to increased trade flows, as well as benefiting from increased foreign direct investment (FDI) inflows. This paper analyses the impacts of a range of trade agreements and FDI inflows on Vietnamese trade flows. We offer new insights through considering which of the key trade agreements have been more efficient in expanding Vietnamese trade, and how the sensitivity of trade to FDI has changed as a result. The estimation of gravity models over a 1996-2014 study period indicates that the bilateral trade agreements with the US and Japan have resulted in the most notable expansion of Vietnamese exports and imports, while the impacts from other regional trade agreements involving Vietnam are more mixed. We also find evidence of Vietnamese trade and FDI being complementary, with the positive relationship between FDI and exports becoming stronger following the bilateral trade agreements with the US and Japan. Keywords: Trade Liberalisation, Trade, Foreign Direct Investment JEL Classifications: F13, F14, F15, F21 DOI: https://doi.org/10.32479/ijefi.7767